New approach to the synthesis of bromochloromethane as a biocide intermediate - Muthusubramanian, L.; Mitra, Raiat B. (Journal of the Society of Leather Technologists and Chemists, 2005)
Preservatives are essential in the leather industry in particular to protect wet tanned and crust leather against mould damage. Preservative selection is made on the basis of ecological and toxicological aspects, statutory requirements, official regulations and their effectiveness and cost. Until legislation restricted the use of pentachlorophenol (PCP), phenolics were the predominant wet blue fungicides, but afterwards Busan 30L (Buckman Laboratories) was widely adopted in the industry. The active ingredient of Busan 30L is 2-(thiocyanomethyl)-thiobenzothiazole (TCMTB). This paper reports the synthesis of bromochloromethane (BCM) which is an important intermediate for the synthesis of TCMTB. The process which we have developed is simple and offers cleaner, low-waste technology for the synthesis of BCM using non-toxic and non-hazardous raw materials. The BCM was characterized by conventional methods, IR, (HNMR)-H-1 and mass spectra data.